2020
DOI: 10.55713/jmmm.v30i4.871
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic sensors and geometrical magnetoresistance: A review

Abstract: Magnetic sensing devices are of the extremely significant kind of detectors, that are used several important and useful applications. Geometrical extraordinary magnetoresistance (EMR) is the geometrical kind of magnetoresistance associated with the non-magnetic semiconductor-metal hybrid structure and influenced by geometrical shape. As a result of Lorentz force, the current path change from metal (in absence of magnetic field) to semiconductor (under the subjection of the magnetic field) in semiconductor-meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 133 publications
1
3
0
Order By: Relevance
“…The EDX analysis showed that the calcium to phosphorous (Ca/P) ratio varies from 1.67 to 1.70, which is in good agreement with the standard value (1.4-2.4 Ca/P ratio of stable HAp). [4,47] This confirms that the HAp obtained can be regarded as a bone-like apatite. [34,43] The morphology and in-depth HAp structure were studied by FE-SEM analysis.…”
Section: Chemical and Morphological Evolution Of Hap With Thermal Tre...supporting
confidence: 66%
See 1 more Smart Citation
“…The EDX analysis showed that the calcium to phosphorous (Ca/P) ratio varies from 1.67 to 1.70, which is in good agreement with the standard value (1.4-2.4 Ca/P ratio of stable HAp). [4,47] This confirms that the HAp obtained can be regarded as a bone-like apatite. [34,43] The morphology and in-depth HAp structure were studied by FE-SEM analysis.…”
Section: Chemical and Morphological Evolution Of Hap With Thermal Tre...supporting
confidence: 66%
“…[41] The medium absorbance peak at 632.65 cm −1 indicates the deformation and vibrational mode of the OH group present in HAp. [44][45][46][47] The presence of phosphate group and hydroxyl group in FTIR spectra implies that HAp is present in the calcined powder.…”
Section: Chemical and Morphological Evolution Of Hap With Thermal Tre...mentioning
confidence: 99%
“…This behavior is attributed to the low concentration of the magnetic center in the sample (Fe 3+ ), and the diamagnetic polymer between the magnetic center resists the interaction between the magnetic centers. Therefore a diamagnetic behavior is observed in sample PPFe-7Zn [43][44][45][46].…”
Section: Magnetic Propertiesmentioning
confidence: 86%
“…The magnetoresistive effect involves a change in the electrical resistance of a structure when a magnetic field is applied. This variation is quantified by the magnetoresistance ratio (MR) and can occur in non-magnetic semiconductor–metal hybrid structures [ 2 ], metals [ 3 ], and magnetic metals [ 4 ] or in multilayer systems such as magnetic tunnel junctions (MTJs) and giant-magnetoresistance, colossal-magnetoresistance, and extraordinary-magnetoresistance structures. Among magnetoresistive structures, those based on the tunnel magnetoresistance effect have a higher MR and better spatial resolution [ 5 , 6 , 7 ], which recommends them for various applications [ 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%